THE IMPLEMENTATION OF THE AWARENESSENLIGHTMENT IN INTERPRETATION (ATTAW’IYYAH WA AT-TANWĪR) AND SOCIAL MOVEMENT (TAḤRĪK AL-MUJTAMA‘) FROM THE PERSPECTIVE OF SEYYED ALI KHAMENEI - Achmad Fadel (Sadra International Institute, 2023)
This research aims to implement the Quranic interpretation approach of Sayyid Ali Khamenei based on awareness-enlightenment interpretation (at-taw’iyyah wa at-tanwīr) and social movement (taḥrīk al-mujtama‘) within society. Ali Khamenei’s approach to understanding the Qur'an is a distinctive feature that he applies in his lessons of interpretation during his time in Mashhad with the hawza students and university students. The phases of his life journey demonstrate an exceptionally close relationship with the Qur'an.he interpretive approach utilized by Ali Khamenei actually shares similarities with other scholars of interpretation, such as Muhammad Abduh, Seyyed Qutb, Mustafa Maraghi, Thahir bin Ashur, Seyyed Hossein Fadlullah, Nasir Makarim Shirazi, and others. These scholars approach the Qur’an with a blend of literary and social context, often referred to as